Hiperrealitas Belanja Online Pada Mahasiswa Universitas Muhammadiyah Malang - Rido Anshari Azmi (Sosioglobal, 2022)
Hyperreality indicates that the old reality has died and been replaced by a new reality where this can be seen from the pervasiveness of pseudo reality which is difficult to distinguish from the real one. This pseudo reality is an e-commerce’s world where many people find it easy to access and get a product of what they need only through internet devices and smart devices that can be accessed anywhere and anytime. Students are probably one of the e-commerce users who get a lot of convenience and can also save time when accessing e-commerce platforms on their smart devices. This study uses a qualitative approach with the type of phenomenological research where researchers identify human experiences about a particular phenomenon that is being studied. Collecting data using the methods of observation, interviews, and documentation. The research subject itself involved students from the University of Muhammadiyah Malang. Data analysis using the Moustakas method. This study uses the theory of hyperreality from Jean Baudrillard which explains that there are three stages of the subject before entering hyperreality, namely the stages of simulation, simulacra, and simulacrum. Simulation is an e-commerce, simulacra is the equivalent of sign manipulation that requires a reference model to identify oneself, while in simulacrum the subject has lost his identity because he has become the reference model of himself. Based on the results of research on e-commerce that occurs among students, there is a hyperreality that occurs due to lifestyle factors that always align with their friendship environment and are also influenced by activities on social media where users are always offered product display advertisements. Hyperreality can be seen from those who have consumptive behaviours where they buy an item not based on what they need, but based on their sheer desire to affirm their social class. Keywords: Hyperreality, E-commerce, Simulation, Simulacra, Simulacrum